Dodgeball: A Virtual Reality Sport Game Using Kinect And XNA Game Studio - Erick Leonardo; Liliana -; Kartika Gunadi (Jurnal Infra, 2015)
Technology development, particularly in video game, has reached to all human life aspects. Many game developers seek not only for innovations to a more interesting gaming system, but also for added values to the game itself. Virtual reality game becomes one of the alternatives to develop the gameplay aspect. Players are highly immersed in the video game world, and convinced as if they were in the game itself. This thesis aims to make a virtual reality game with Dodgeball sport theme using Kinect and XNA Game Studio integrated development environment.The Kinect used in this Dodgeball game is meant to control a game character to follow the real one. The character moves in the same way in real life. Therefore, players will find the game more realistic, and they will feel the sensation of playing the real Dodgeball. Besides, players do not need to use a game controller. Players’ movement also become more natural in the absence of the game controller.Our Dodgeball game has gone through several adjustments, such as, each team’s players are limited to 4 people, which at most 2 of them are human players. The number of balls used in this game is reduced to 2, and before the game begins, the balls are assigned to teams by coin tosses. Dodgeball game is also packed with physics and simple artificial intelligence to enhance players’ gaming experiences in playing Dodgeball game.